Childhood Glaucoma - Mahar, P. S. (Pakistan Journal of Ophthalmology, 2018)
Childhood glaucoma is a heterogeneous cluster of disorders occurring in early years of life. According to the American Academy of Ophthalmology1, congenital glaucoma is present at birth or diagnosed up to 12 months of life. Infantile glaucoma is present from 1 year to 3 years and after 3 years onwards, it is termed as juvenile glaucoma. This division however can be arbitrary in our country where child is brought often too late for clinical advice. Most of the pediatric glaucoma have no specific identifiable cause and are considered as primary glaucoma. However, when glaucoma is associated with some specific disease, it is called as secondary glaucoma. Some of the disorders associated with childhood glaucoma include Axenfeld – Rieger syndrome, Sturge-Weber syndrome, Aniridia and Neurofibromatosis. The chronic use of topical steroids, trauma and cataract surgery remain the other associated factors